Curbing capital flight : an analysis of Illicit financial flows in South Africa’s mining industry - Ngobeni, Tinyiko (University of Pretoria, 2025)
Mini Dissertation (LLM (International Trade and Invetsment Law in Africa))--University of Pretoria 2025.